On the reactive coagulation of incipient soot nanoparticles. (January 2022) - Hou, Dingyu; Pascazio, Laura; Martin, Jacob; Zhou, Yuxin; Kraft, Markus; You, Xiaoqing
Abstract: In this work, we studied the coagulation process of two PAH clusters with diameter ∼ 2 nm using reactive molecular dynamics (MD) simulations. To describe the coagulation process quantitatively, the distance between the center of mass (COM) of the two PAH clusters, as well as the inter-cluster potential energy and kinetic energy of the COM of the clusters were calculated. Head-on coagulation efficiencies ( η ) of two PAH clusters at typical flame temperatures where soot inception is most likely to occur, i.e., 1500 K—2000 K, were determined based on hundreds of MD simulated trajectories. Our simulation results showed that η decreases with increasing temperature, which is mainly due to the increased kinetic energy of atoms within the PAH clusters at higher temperature. In addition, introduction of surface σ -radical site fraction in the range of 0.01 to 0.1 can only moderately improve η by ∼ 10% by forming carbon–carbon bonds between the two coagulating clusters, which suggests η of incipient soot nanoparticles with surface σ -radicals in high temperature flame regions is very low even if with reactive coagulation taken into consideration. Graphical abstract: Highlights: Reactive MD simulations have been performed to study the coagulation efficiency η of incipient soot nanoparticles at T ≥ 1500 K. Head-on coagulation efficiency η has been determined based on hundreds of MD simulated trajectories. σ -radicals on soot surface have been found to mildly enhance η by ∼ 10% through C-C bond formation between the nanoclusters.